Analysis of the Level of Political Participation of the Kenduri Cinta Community in Jakarta - Rahayu, Eka; Nurwahidin, Nurwahidin; Chotib, Chotib (International Journal of Social Service and Research, 2023)
This research was conducted to determine the level of political participation of the Kenduri Cinta community as an urban Sufism community in DKI Jakarta. The method used in this research is a quantitative method by distributing questionnaires to the Kenduri Cinta community who were selected by purposive sampling. The independent variables used in this research are political concern; political motivation; political situation and environment; political education; and political orientation. This study explains how these independent variables affect the political participation of the Kenduri Cinta community. The 503 questionnaires obtained were processed by the SPSS application version 25. The Principal Component Analysis method was used in multiple linear regression to analyse how independent variables affect their political participation. The F test result shows that all independent variables simultaneously affect the level of political participation of the Kenduri Cinta community. Meanwhile, the t test result shows that four independent variables are significant and three of them have positive regression coefficients. Interestingly, political motivation has a negative regression coefficient even though it is significant. This means the higher their political motivation, the lower their political participation.